2022
DOI: 10.1038/s41598-022-14359-8
|View full text |Cite
|
Sign up to set email alerts
|

Shared and distinct voxel-based lesion-symptom mappings for spasticity and impaired movement in the hemiparetic upper limb

Abstract: Hemiparesis and spasticity are common co-occurring manifestations of hemispheric stroke. The relationship between impaired precision and force in voluntary movement (hemiparesis) and the increment in muscle tone that stems from dysregulated activity of the stretch reflex (spasticity) is far from clear. Here we aimed to elucidate whether variation in lesion topography affects hemiparesis and spasticity in a similar or dis-similar manner. Voxel-based lesion-symptom mapping (VLSM) was used to assess the impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 112 publications
1
4
0
Order By: Relevance
“…Family-wise error rate (FWER) was controlled using the false discovery rate (FDR) method 80 with p-value < 0.05. Due to the relatively small sample size, we also reported voxels that did not survive these corrections, but instead survived a more lenient criterion of p < 0.01, similarly to previous reports [14][15][16][17][18]70 . To explore the extent of anatomical overlap between brain voxels implicated in finger-individuation and strength in each direction (flexion, extension), we employed VLSM conjunction analysis contrasting brain voxels that were selectively associated with either flexion or extension, and brain voxels without such direction selectivity (i.e., voxels in which the existence of damage affected performance in both flexion and extension).…”
Section: Brain Imaging and Voxel-based Lesion-symptom Mappingsupporting
confidence: 86%
See 2 more Smart Citations
“…Family-wise error rate (FWER) was controlled using the false discovery rate (FDR) method 80 with p-value < 0.05. Due to the relatively small sample size, we also reported voxels that did not survive these corrections, but instead survived a more lenient criterion of p < 0.01, similarly to previous reports [14][15][16][17][18]70 . To explore the extent of anatomical overlap between brain voxels implicated in finger-individuation and strength in each direction (flexion, extension), we employed VLSM conjunction analysis contrasting brain voxels that were selectively associated with either flexion or extension, and brain voxels without such direction selectivity (i.e., voxels in which the existence of damage affected performance in both flexion and extension).…”
Section: Brain Imaging and Voxel-based Lesion-symptom Mappingsupporting
confidence: 86%
“…We therefore report here for the extension analysis voxels that survived a lenient criterion of p < 0.01 (corresponding to minimal z-score of 2.32). For a similar approach see 14,[16][17][18] . The cluster peak z-score (z = 3.26) was situated within M1-CST (8% of the cluster; MNI coordinates: -28 -16 48), while its periphery also overlapped with SLF-II (30%), M1 (19%), CRP (14%), and PM-CST (5%).…”
Section: Impact Of Lesion Topography On Finger Individuation Vlsm Rev...mentioning
confidence: 99%
See 1 more Smart Citation
“…The current results did not observe interhemispheric connectivity to be significantly associated with any of the grip measures. These findings may indicate how lesion location leads to functional deficits to somatosensation [ 77 , 78 ], motor performance [ 79 , 80 ], and subsequent recovery outcomes [ 81 ]. Heightened involvement or activity of the non-lesioned hemisphere relative to the lesioned hemisphere may indicate either the presence of compensatory mechanisms or bilateral drive needed to control paretic arm movement after stroke [ 82 , 83 , 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that compared to the HCs, ReHo changed in the left putamen of the BGIS group in the conventional frequency band. Putamen as a nucleus of the BG was located near the motor never tracts of the brain ( Frenkel-Toledo et al, 2022 ). Damage to the corticospinal tract in the putamen would affect lower limb motor function of patients with stroke ( Frenkel-Toledo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%